Executive Overconfidence and Corporate Tax Strategy: Evidence from Emerging Markets - Haryanto Haryanto; Eva Herianti; Amor Marundha; Rino Dwi Putra (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines how accounting-based tax strategies operate within managerial accounting, accounting for executive cognition, and whether they are applied uniformly or selectively. Methodology: This study employs a quantitative panel data design using 22 publicly listed manufacturing firms in Indonesia over the 2020–2023 period, yielding 81 firm-year observations after outlier removal. Fixed effects estimation is applied to analyze the relationships between transfer pricing, real earnings management, thin capitalization, and tax management, proxied by the Cash Effective Tax Rate, with CEO overconfidence as a moderating variable. Results: The findings show that accounting-based tax strategies do not operate uniformly across firms. Transfer pricing is positively associated with tax management, whereas real earnings management is linked to lower tax burdens. Thin capitalization does not exhibit a significant relationship. CEO overconfidence selectively moderates these relationships, weakening the effectiveness of transfer pricing and strengthening the association between real earnings management and tax management. Conclusions: The results indicate that tax management is a behavioral process shaped by executives' perceptions of control and discretion within institutional constraints. Limitations: The analysis is limited to manufacturing firms in a single emerging economy (Indonesia) and relies on an indirect proxy for the measurement of executive cognition. Contributions: This study contributes to the behavioral accounting and tax management literature by showing that executive cognition shapes the selective use of accounting-based tax strategies.